2018
DOI: 10.3389/fpls.2018.00647
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of Silicon Bioavailability, Uptake, Transport, and Accumulation: Applicability in Improving the Nutritional Quality of Tomato

Abstract: Silicon is an essential nutrient for humans, additionally is beneficial for terrestrial plants. In plants Si enhances tolerance to different types of stress; in humans, it improves the metabolism and increases the strength of skeletal and connective tissues as well as of the immune system. Most of the Si intake of humans come from edible plants creating a double benefit: first, because the absorption of Si increases the antioxidants and other phytochemicals in plants, thereby increasing its functional value, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…This would explain the strong differences in Si concentration reported within tissues of different plants species [ 141 ]. In any case, Si is taken up by the roots as monosilicic acid with the involvement of channels belonging to the aquaporins’ group, so the water flow resulting from leaf transpiration seems to play a determinant role in defining the rate of Si absorption and transport within the plant [ 142 ]. Once absorbed, monosilicic acid is subsequently translocated to the shoot through the xylem flow, where Si is concentrated thanks to transpiration and polymerized to silica (SiO 2 ), then deposited in the different tissues [ 143 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
See 2 more Smart Citations
“…This would explain the strong differences in Si concentration reported within tissues of different plants species [ 141 ]. In any case, Si is taken up by the roots as monosilicic acid with the involvement of channels belonging to the aquaporins’ group, so the water flow resulting from leaf transpiration seems to play a determinant role in defining the rate of Si absorption and transport within the plant [ 142 ]. Once absorbed, monosilicic acid is subsequently translocated to the shoot through the xylem flow, where Si is concentrated thanks to transpiration and polymerized to silica (SiO 2 ), then deposited in the different tissues [ 143 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…Plants markedly differ in their ability to accumulate Si in their various organs; concentrations ranging between 5 and 50 g kg −1 DW have been reported as critical for some species. The species with low mobilization capacity accumulate it in the roots and stems, while the species with high mobilization capacity accumulate Si in stems, leaves, fruits, and seeds [ 142 ]. Gao et al [ 145 ] noticed that excessive Si supply (>2 mM) caused the formation of Si polymers on root surfaces, a feature that could affect nutrients uptake.…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…No correlation between soil and leaf samples for plant-available Si could be the consequence of the changes in its availability during the growing season, as the solubility of silica in the soil is affected by soil processes, soil pH, the presence of organic complexes and aluminium, iron, and phosphate ions, dissolution reactions, and soil moisture (Rao et al 2017). In spite of the lower total soil Si content in the alpine heath soil from below the summit of Mount Komen, one would assume that the soil from this habitat was richer in plant-available Si, as it has been shown that the bioavailability of Si can increase with greater soil organic matter content (López-Pérez et al 2018). However, this was not the case here.…”
Section: Discussionmentioning
confidence: 73%
“…Significant quantity of silicon present in the soil makes it the second most abundant element on the earth’s crust, and hence studies were carried out to understand its role in the rhizosphere. It was discovered that silicon could not only increase the biomass production but also had role in enhancing tolerance to biotic and abiotic stresses, thus supporting plants with stability and protection ( Luyckx et al, 2017 ; López-Pérez et al, 2018 ). Interestingly, a study also discovered silicon uptake transporters from some legumes like soybean which were similar to the silicon transporters in hyper accumulating grasses ( Deshmukh et al, 2013 ).…”
Section: Role Of Silicon In Plant–microbe Interactionmentioning
confidence: 99%